Bone Adaptation In Silico Approach - Kameo, Yoshitaka (Frontiers of Biomechanics,, 2018)
This book focuses on the systems biomechanics of bone remodeling that provide a multiscale platform for bone adaptation, spanning the cellular, tissue, and organ levels. The mathematical model explained in each section provides concrete examples of in silico approaches for bone adaptation. It will be immensely useful for readers interested in bone morphology and metabolism and will serve as an effective bridge connecting mechanics, cellular and molecular biology, and medical sciences. These in silico approaches towards exploring the mechanisms by which the functioning of dynamic living systems is established and maintained have potential for facilitating the efforts of graduate students and young researchers pioneering new frontiers of biomechanics.